2009
DOI: 10.1097/ruq.0b013e3181981df0
|View full text |Cite
|
Sign up to set email alerts
|

Hypervascular Synovitis and American College of Rheumatology Classification Criteria as Predictors of Radiographic Damage in Early Rheumatoid Arthritis

Abstract: Serial Power Doppler ultrasonography-assessed synovitis was greater in patients who developed erosions than in those who did not. More power Doppler positive (hypervascular) synovitis and more ACR classification criteria, both at baseline, were the only predictors of erosions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…These data were in agreement with another study about a 2-year follow-up of RA patients, showing that the degree of synovial hyperaemia at baseline and the number of ACR criteria were the only predictive factors for the development of erosions [38]. More recently, a study applying MRI, PDUS, CT scan and radiography on 52 RA patients on therapy with adalimumab and MTX demonstrated the lack of clear evidence that subclinical synovitis is responsible for radiological progression; however, PDUS-detected synovitis as well as bone oedema at baseline have been found to be risk factors for erosions [39].…”
Section: Predictive Value Of Dopplersupporting
confidence: 92%
“…These data were in agreement with another study about a 2-year follow-up of RA patients, showing that the degree of synovial hyperaemia at baseline and the number of ACR criteria were the only predictive factors for the development of erosions [38]. More recently, a study applying MRI, PDUS, CT scan and radiography on 52 RA patients on therapy with adalimumab and MTX demonstrated the lack of clear evidence that subclinical synovitis is responsible for radiological progression; however, PDUS-detected synovitis as well as bone oedema at baseline have been found to be risk factors for erosions [39].…”
Section: Predictive Value Of Dopplersupporting
confidence: 92%
“…Two LQ studies showed the same trend in the data, but statistical significance was not achieved (table 3). 18 25…”
Section: Resultsmentioning
confidence: 99%
“…Third, synovial hypertrophy was present more frequently in patients with erosive abnormalities, confirming the well‐established concept that its presence is an independent risk factor for the development of erosive arthropathy (). Furthermore, the presence of hypervascular synovitis is a stronger predictor for radiologic damage and US erosions (). Finally, the high prevalence of osteophytes in patients with RA with respect to healthy controls (29% versus 12%) could be the expression of the simultaneous presence of inflammatory and degenerative changes, such as in data reported for distal interphalangeal joints in patients with RA ().…”
Section: Discussionmentioning
confidence: 99%